A single exposure of sediment sulphate-reducing bacteria to oxytetracycline concentrations relevant to aquaculture enduringly disturbed their activity, abundance and community structure - Fernández Montes de Oca, María Laura (2015)
Aim: although feed medicated with antibiotics is widely used in animal production to prevent and treat bacterial infections, the effect of these drugs on nontarget anaerobic bacteria is unknown. We aimed to clarify whether a single exposure of sulphate-reducing bacteria (SRB) from a tilapia pond to oxytetracycline (OTC) concentrations relevant to aquaculture impacts their function, abundance and community structure. Methods and Results: to demonstrate changes in SO4 -2 content, SRB abundance, dsrB copy number and SRB diversity, sediment mesocosms were spiked with 5, 25, 50 and 75 mg OTC kg -1 and examined for 30 days by means of ion chromatography, qPCR, cultivation and fluorescent in situ hybridization (FISH). On day 3, we measured higher SO4 -2 concentrations (ca. two-fold) and a reduction in dsrB copy numbers of approximately 50% in the treatments compared to the controls. After 30 days, a subtle yet measurable enrichment of bacteria from the order Desulfovibrionales occurred in mesocosms receiving ≥50 mg OTC kg -1, notwithstanding that SRB counts decreased two orders of magnitude. OTC was dynamically and reversibly converted into 4-epioxytetracycline and other related compounds in a dosedependent manner during the experiment. Conclusions: a single exposure to rather high OTC concentrations triggered functional and structural changes in a SRB community that manifested quickly and persisted for a month. Significance and Impact of the Study: This study improves our limited knowledge on the ecotoxicology of antibiotics in anaerobic environments.